Genome‐wide association studies of the self‐rating of effects of ethanol (SRE). (3rd July 2019) - Lai, Dongbing; Wetherill, Leah; Kapoor, Manav; Johnson, Emma C.; Schwandt, Melanie; Ramchandani, Vijay A.; Goldman, David; Joslyn, Geoff; Rao, Xi; Liu, Yunlong; Farris, Sean; Mayfield, R. Dayne; et al.
Abstract: The level of response (LR) to alcohol as measured with the Self‐Report of the Effects of Alcohol Retrospective Questionnaire (SRE) evaluates the number of standard drinks usually required for up to four effects. The need for a higher number of drinks for effects is genetically influenced and predicts higher risks for heavy drinking and alcohol problems. We conducted genome‐wide association study (GWAS) in the African‐American (COGA‐AA, N = 1527 from 309 families) and European‐American (COGA‐EA, N = 4723 from 956 families) subsamples of the Collaborative Studies on the Genetics of Alcoholism (COGA) for two SRE scores: SRE‐T (average of first five times of drinking, the period of heaviest drinking, and the most recent 3 months of consumption) and SRE‐5 (the first five times of drinking). We then meta‐analyzed the two COGA subsamples (COGA‐AA + EA). Both SRE‐T and SRE‐5 were modestly heritable ( h 2 : 21%‐31%) and genetically correlated with alcohol dependence (AD) and DSM‐IV AD criterion count ( r g : 0.35‐0.76). Genome‐wide significant associations were observed (SRE‐T: chromosomes 6, rs140154945, COGA‐EA P  = 3.30E‐08 and 11, rs10647170, COGA‐AA+EA P  = 3.53E‐09; SRE‐5: chromosome13, rs4770359, COGA‐AA P  = 2.92E‐08). Chromosome 11 was replicated in an EA dataset from the National Institute on Alcohol Abuse and Alcoholism intramural program. In silico functional analyses and RNA expression analyses suggest that the chromosome 6 locus is an eQTL for KIF25 . Polygenic risk scores derived using the COGA SRE‐T and SRE‐5 GWAS predicted 0.47% to 2.48% of variances in AD and DSM‐IV AD criterion count in independent datasets. This study highlights the genetic contribution of alcohol response phenotypes to the etiology of alcohol use disorders. Abstract : We performed GWAS of the Self‐Report of the Effects of alcohol (SRE) scores using COGA samples. Three loci were genomewide significant and one was replicated. Functional analyses suggested that the chromosome 6 locus is an eQTL for KIF25. COGA SRE GWAS derived polygenic risk scores predicted variances in alcohol dependence (AD) and DSM‐IV AD criterion count. This study highlights the genetic contribution of SRE to the etiology of alcohol use disorders.